1990
DOI: 10.1002/ange.19901021106
|View full text |Cite
|
Sign up to set email alerts
|

Falsche Annahmen über die Zusammenhänge zwischen der Umweltverschmutzung und der Entstehung von Krebs

Abstract: In der Offentlichkeit gibt es zahlreiche falsche Vorstellungen iiber die Zusammenhange zwischen Umweltverschmutzung und Krebs beim Menschen. Grundlage dafiir ist die irrige Auffassung, daB von der Natur nur Gutes ausgehe. In diesem Beitrag werden acht Fehleinschatzungen herausgegriffen und wissenschaftlichen Erkenntnissen gegeniibergestellt. Fehleinschatzung

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…As yet there have been no studies on this. Ames tests [482] were carried out on some simple b-amino acids and were found to be negative [219]. It has also been found that neither b 2 -nor b 3 -homoarginine function as substrates for the NO synthetases [483], which is perhaps not too surprising, since even the enantiomer of (S)-arginine itself is not accepted [484].…”
Section: Paul Tillichmentioning
confidence: 99%
“…As yet there have been no studies on this. Ames tests [482] were carried out on some simple b-amino acids and were found to be negative [219]. It has also been found that neither b 2 -nor b 3 -homoarginine function as substrates for the NO synthetases [483], which is perhaps not too surprising, since even the enantiomer of (S)-arginine itself is not accepted [484].…”
Section: Paul Tillichmentioning
confidence: 99%